Analysis of online dual-channel supply chain based on service level of logistics and national advertising. Issue 4 (1st October 2016) - He, Li-hong; Liao, Xi; Zhang, Zhe George; Haug, Peter
Abstract: With the fast growth of e-commerce, not only many manufacturers have engaged in direct online sales, but also retailers enter the e-commercial market to increase their sales. In addition, due to the computer literacy penetration, more consumers are willing to make purchases online for convenience and time saving. In practice, manufacturers may have two web-based selling channel options, selling products through e-retailers or selling products directly to customers through their own websites. In this paper, we consider an online dual-channel supply chain consisting of one manufacturer and one e-retailer, in which customers can purchase products from either the e-retailer channel or the manufacturer's website channel. Such a two-channel system not only creates unprecedented opportunities, but also adds new competition between the manufacturer and e-retailer channels. This paper focuses on the strategies of the manufacturer and the e-retailer under two price decision models, pricing uniformly by the manufacturer or pricing separately. We also consider the effect of the national advertising, which can stimulate potential purchase behaviour to some degree. It is assumed that the demand is simultaneously influenced by price and logistics service level. We find that the logistics level is proportional to the e-retail price under four different models. In addition, the logistics service level positively influences the national advertising expenditure of the manufacturer. Using numerical analysis, we find that when the manufacturer decides to invest in the national advertising and both players of supply chain set price separately, both the supply chain and customers can achieve a win-win situation if the e-retailer improves its bargaining power.